Ransacking the wordhord: the stylistic use of Old English lexical borrowings in Viking Age skaldic poetry - Gunn, N (Brepols Publishers, 2020)
This chapter assesses the use of a small selection of Old English loanwords in Viking Age skaldic verse (hearra/harri, heretoga/hertogi, sāwol/sála, godfæder/goðfaðir). Drawing on modern sociolinguistic and stylistic theory, it argues that the perceived "Englishness" of these lexical borrowings is less interesting than the way they were used creatively in performance to elicit certain artistic, cognitive and ideological effects.